Hernán Díaz. Borges, between History and Eternity. London/New York: Continuum, 2012. 208 pp - Daniel Altamiranda (Studies in 20th & 21st Century Literature, 2014)
Review of Hernán Díaz. Borges, between History and Eternity. London/New York: Continuum, 2012. 208 pp.
Keywords: Jorge Luis Borges